6 - Le Parlement congolais post-élection dans le processus de construction de l’espace public : mythe ou réalité ? https://doi.org/10.4314/ad.v35i4.70219 - Tukala Célestin Tshimande (Africa Development, 2021)
Since 2007, the DRC has had a Parliament established by free, pluralistic, demo- cratic, transparent and credible elections. It has been hard at work since then and has legislated and debated numerous questions, of which the most important seem to be the issue of nationality, which was at the root of both armed conflicts experienced by the country. Despite the organization of elections, the establish- ment of an elected Parliament and the existence of a law on nationality, the nationality problem still subsists. The law itself is not respected by the authori- ties, which are externally controlled. This has caused a stir and forced the parlia- ment to launch a moratorium that was never enforced. Parliament addressed the issue, which was debated, but parliament did not find a solution to the issue of the moratorium. There was also the issue of the violent incidents opposing the national police of Congo (PNC) and the Bandu Dia Kongo (BDK) in Matadi and the Luozi territories, Seke Banza and Lukula, in February and March 2008. The BDK was accused of assuming state powers in several villages where PNC presence was very limited. The Government therefore launched operations to restore the authority of the state throughout the Lower Congo. These operations soon took on a dimension of excessive use of force, arbitrary executions, systematic destruc- tion of BDK churches and houses, in addition to a large number of arbitrary arrests. Other questions emerge, notably the crash of the ‘Antonov’ airplane, which revealed the lack of strict legislation in the transport sector, which is also vital for the security of the population, and that of the cooperation agreement between the DRC and a Chinese business organization. It is clear from the debates on the issues discussed in parliament that there is an obvious lack of interest for the establishment of real political, economic and social democracy. This presentation explicitly seeks to fully and concretely analyse through specific examples the quality of debates in parliament to determine whether it can contribute to the construction of public space.